A qualitative study on healthcare professional and patient perspectives on nurse-led virtual prostate cancer survivorship care - Karen Young; Ting Xiong; Kaylen J. Pfisterer; Denise Ng; Tina Jiao; Raima Lohani; Caitlin Nunn; Denise Bryant-Lukosius; Ricardo Rendon; Alejandro Berlin; Jacqueline Bender; Ian Brown; et al. (Communications Medicine, 2023)
Abstract Background Virtual nurse-led care models designed with health care professionals (HCPs) and patients may support addressing unmet prostate cancer (PCa) survivor needs. Within this context, we aimed to better understand the optimal design of a service model for a proposed nurse-led PCa follow-up care platform (Ned Nurse). Methods A qualitative descriptive study exploring follow-up and virtual care experiences to inform a nurse-led virtual clinic (Ned Nurse) with an a priori convenience sample of 10 HCPs and 10 patients. We provide a health ecosystem readiness checklist mapping facilitators onto CFIR and Proctor’s implementation outcomes. Results We show that barriers within the current standard of care include: fragmented follow-up, patient uncertainty, and long, persisting wait times despite telemedicine modalities. Participants indicate that a nurse-led clinic should be scoped to coordinate care and support patient self-management, with digital literacy considerations. Conclusion A nurse-led follow-up care model for PCa is seen by HCPs as acceptable, feasible, and appropriate for care delivery. Patients value its potential to provide role clarity, reinforce continuity of care, enhance mental health support, and increase access to timely and targeted care. These findings inform design, development, and implementation strategies for digital health interventions within complex settings, revealing opportunities to optimally situate these interventions to improve care.